Virtually connected in a multiverse of madness? - Perceptions of gaming, animation, and metaverse - Oliveira, A.; Cruz, M. (Applied Sciences, 2023)
Few studies analyze what are the common representations of the Metaverse. Regarding what has been said about this concept, our research aims to verify how adults percept and represent the Metaverse. We carried out a study with focus groups, having as participants Portuguese adults all considered habitual gamers (or users of digital games). The objectives for this study were seven: verify how the Metaverse is being represented and characterized; identify which technologies stimulate the immersion experience; identify the main dimensions that influence the acceptance of the Metaverse concept; understand the perceptions of Metaverse and virtual reality regarding socialization and well-being; verify the perceptions of a gamer’s daily lives regarding the Metaverse, virtual reality, and gaming concepts; understand the impact of social representations on the gaming concept; to understand the perceived role of animation regarding the Metaverse, virtual reality, and gaming concepts. Our results reveal a common understanding of the Metaverse, despite some confusion about this concept. We also verified the high importance of well-being and social dimensions in the Metaverse immersive experiences provided by technology or gaming characteristics. This exploratory study gave us essential findings about the perceptions of the Metaverse and a deep understanding of the relations between Metaverse, virtual reality, animation, and gaming.